Optimal control for discrete and continuous stochastic descriptor systems with application to a factory management model - Shu, Yadong; Li, Bo (International journal of control, 2023)
In this paper, optimal control models ruled by discrete and continuous stochastic descriptor systems are investigated in order. These descriptor systems are assumed to be regular and impulse-free. For settling discrete optimal control problems, a recurrence equation is proposed with the help of dynamic programming method. Then, optimal control problems for two types of discrete stochastic descriptor systems are considered and optimal solutions are presented by analytical expressions. To simplify continuous optimal control problems, an equation of optimality is derived according to the principle of optimality, and it reveals the essential connection between optimal value and optimal control. Two numerical examples and a factory management model are provided to illustrate the validness of above results.